Sediment sources and transport pathways of dune sands, western Sandomierz Basin (Southern Poland) - Goździk, Jan; Gruszka, Beata (Geologos, 2025)
Aeolian dune fields of the European Sand Belt extend across Poland, yet their southern limit coincides with the Sandomierz Basin, where potential sand sources from the Małopolska Upland and the Carpathians converge. This study uses quartz-grain morphology to constrain the provenance of dune sands in the western Sandomierz Basin and to assess Late Pleniglacial (MIS 2) aeolian–fluvial interactions. Sediments were sampled from aeolian dunes, fluvial terraces and outwash plains across c. 2,500 km², including the Vistula and its tributaries (Dunajec, Raba, Rudawa and Przemsza) and adjacent uplands. Stratigraphic ages were assigned using the Detailed Geological Map series (1:50,000). Grain roundness was measured on the 0.8–1.0 mm fraction using Krumbein’s scale, and grain-surface textures were classified with the Cailleux morphoscopic approach (NU, EL, RM, EM). Carpathian-river alluvia (Raba, Dunajec) show predominantly subangular to subrounded grains in Early Pleniglacial deposits, indicating limited aeolian abrasion despite long fluvial transport. In Late Pleniglacial alluvia, RM proportions increase markedly and roundness distributions become bimodal, reflecting enhanced aeolian reworking during the coldest MIS 2 phases. In contrast, Vistula and upland-tributary alluvia contain higher RM contents and more rounded grains, consistent with recycling of sands previously modified by long-distance aeolian transport on the Małopolska Upland. Dune deposits display strong spatial variability: the northern dune zone adjacent to the Vistula is dominated by Vistula-like, well-rounded RM grains, whereas southern dune clusters (Raba Fan, Raba–Dunajec interfluve, Tarnów Plateau) record mixed contributions, locally modulated by river corridors and topographic barriers that constrained aeolian pathways. Quartz-grain morphology thus provides an effective, low-cost proxy for distinguishing upland versus Carpathian sand sources and for reconstructing short-range transport pathways and sediment mixing within coupled aeolian–fluvial systems during the Late Pleniglacial.